Longitudinal Changes in the Government-Certified Index Stage and Requisite Costs for Long-Term Care Insurance System among the Community-Dwelling Demented Elderly in Japan. (28th February 2013) - Shinagawa, Shunichiro; Nakamura, Shiori; Iwamoto, Makoto; Tsuno, Norifumi; Shigeta, Masahiro; Nakayama, Kazuhiko
Abstract : Background . A new public long-term care (LTC) insurance was launched in 2000 in Japan. However, there have been few studies involving factors that increase LTC costs of demented subjects; no follow-up studies involving the Government-Certified Index (GCI) and requisite costs related to the causes of dementia. Method . An epidemiological survey was conducted in a rural area in Japan in 1999, and 271 subjects were diagnosed as dementia patients. Age, sex, mini-mental state examination, clinical dementia rating, activity of daily living, causes of dementia, and coexisting physical disease were confirmed. After the LTC insurance has been launched, we tracked the GCI stages and payment amounts every month for 8 years. Result . 209 subjects were certified to be eligible for LTC insurance; however, 13 did not receive any payment. Only 49 out of 209 were alive after the follow-up period. The most common cause of dementia was Alzheimer's disease (AD), followed by vascular dementia (VaD). There was no significant difference between the mortality rates of the two groups. VaD subjects required higher costs than AD subjects in the total certified period and in GCI stage 5. Conclusion . Our results indicate that causes of dementia can have an impact on the requisite costs for the LTC insurance.